Controversies in the Facial Inversion Effect: Face Specificity and Expertise - Gong, J.; Zhang, Y.; Huang, Y.; Feng, J.; Zhang, W.W. (Нейрофизиология, 2014)
This paper reviews studies on the face inversion effect and expertise. It is suggested that the inversion effect be considered as evidence of specific processing in face recognition or expertise of the objects, which meet three prerequisites. Some disputes are also pointed out in the review. It is proposed that further studies should be addressed to the visual differences, physiological basis of cognitive modules, and anatomical and functional location of the respective networks.